Particle size distributions and shape identification of pozzolanic materials via various dimensional representations - David Sinkhonde; Tajebe Bezabih; Derrick Mirindi (Hybrid Advances)
Although pozzolanic materials exhibit unusual particle properties, their particle size distributions and shape identification remain poorly understood. Approximating these geometrical features using simplified plugins is critical for optimising the use of pozzolans in sustainable construction. In this research, we explore the geometrical features of clay brick powder (CBP), fly ash (FA), and teff straw ash (TSA) and predict how these features can influence ordinary Portland cement (OPC) replacement in cement-based composites. We base our research on the plugins in ImageJ, which combine straightforward computational principles and efficient methodology to determine particle shapes of materials. Through the pozzolanic properties and Feret diameters of less than 35 μm for the specimens, we illustrate the capabilities of CBP, FA, and TSA in replacing OPC in cementitious composites. The coefficients of determination greater than 0.79 for area-perimeter plots reveal strong correlations for all the specimens. However, the particles with large particle areas and perimeters lead to reductions in coefficients of determination. The good approximations of geometrical features support the use of CBP, FA, and TSA in cement-based composites and will support further studies in particle properties of pozzolans and cementitious composites.